Capital Structure Adjustment Speed: Evidence From Indonesian Property, Real Estate, and Construction Building Firms - Patricia Steffina Mawitjere; Bertha I. Mundung; Nikolas F. Wuryaningrat (Journal of International Conference Proceedings (JICP), 2022)
This study examines the capital structure based on dynamic trade-off theory in property, real estate, and construction building companies in Indonesia. We have used a data panel from 17 companies over the years 2018 to 2021. There are two stages of testing in this study. First, we estimate the target leverage using Random Effect Model and then find the capital structure adjustment speed using Fixed Effect Model. The results of this study prove that profitability has a negative and significant effect on the company's capital structure, firm size has a positive and significant effect on the company's capital structure, while growth does not influence it. This study also revealed that property, real estate, and construction building companies in Indonesia adjusted their capital structure toward optimal capital structure, where the adjustment speed was 25% per year or took 4 years to achieve their optimal capital structure. This study suggests government policies encouraging people's purchasing power to support economic recovery. Keywords: Capital Structure, Dynamic Trade-Off Theory, Firm Size, Growth, Profitability, Speed of Adjustment.